Older Adults’ Perceptions of Alternative Arthritis Management - Jaron, Heart Angel; Belanizo, Zykia Kit; Bicar, Rayjaylou; Bongot, Joy Marie; Guinamos, Gem Crystal; Javier, Alyssa Nicole; Patalinhug, Anna Lou (Journal of Interdisciplinary Perspectives, 2025)
This qualitative phenomenological study explored the perceptions and lived experiences of older adult women in Barangay Looc, Mandaue City, concerning alternative management strategies for osteoarthritis. Addressing a gap in the literature on culturally rooted non-pharmacological practices, the study aimed to understand how older women managed joint pain without or instead of Western medicine. Using purposive and snowball sampling, six female participants aged 60 and above were selected and interviewed using a semi-structured guide. Data were analyzed through thematic analysis. Results revealed five core insights: (1) the widespread use of culturally embedded self-management practices such as hilot, tuba-tuba, and gabon; (2) significant fear and mistrust of pharmaceutical treatments due to personal or familial trauma; (3) the persistence of complex physical symptoms such as pain, stiffness, and fatigue; (4) the pursuit of partial relief as a sufficient outcome to maintain functionality; and (5) the restoration of agency through functional independence. Although traditional remedies often provided only temporary relief, they were viewed as effective in enabling daily activities and preserving autonomy. These findings emphasize the importance of culturally sensitive, trauma-informed geriatric care and the integration of traditional practices into nursing strategies. The study concludes that recognizing culturally grounded practices supports patient-centered care, improves adherence, and enhances quality of life for older adults with osteoarthritis.